Maternal Risk Factors among Pregnant Women with Miscarriage - Sofia, Norlaila; Fadlyana, Eddy; Irianti, Setyorini; Krisnadi, Sofie; Susiarno, Hadi (Althea Medical Journal, 2024)
Background: Approximately, 4.1% of maternal deaths in Indonesia occur due to miscarriage. Miscarriage might be caused by various factors such as fetal, maternal, and external factors. Monitoring and early detection of maternal factors might prevent miscarriage.  This study aimed to analyze the influence of maternal factors on the incidence of miscarriage. Methods: This was an analytic observational study with a case-control design conducted in Banjar District, South Kalimantan in August–September 2022. Data was collected from the medical records of pregnant women who experienced miscarriage (n=60) and pregnant women who did not (n=120). Data was analyzed using the chi square test and logistic regression. The level of maternal risk factors for the incidence of miscarriage was determined from the odds ratio (OR) value at a 95% confidence interval.Results: The results revealed that parity (p=0.000; OR=2.2), nutritional status (p=0.000; OR=77.1), level of education (p=0.001; OR=3.5), and employment status (p=0.000; OR=8.1) had a significant effect on the incidence of miscarriage.Conclusion: Maternal factors such as parity, nutritional status, education level, and employment status influence on the incidence of miscarriage, therefore, it is essential to educate pregnant women on various factors related to miscarriage.